Cooperative behavior and common pool resources: Experimental evidence from community forest user groups in Nepal. (May 2020) - Bluffstone, Randy; Dannenberg, Astrid; Martinsson, Peter; Jha, Prakash; Bista, Rajesh
Highlights: We examine the external validity of a public goods game in terms of reported forest collective action behaviors. Cooperative individuals report more forest collective action behaviors. Cooperative individuals more likely to make investments. Forest collective action behaviors are correlated with forest quality, and especially regeneration measured as tree seedlings per hectare. Abstract: This paper examines whether cooperative behavior by respondents measured as contributions in a one-shot public goods experiment correlates with reported forest collective action behaviors and forest outcomes, such as more carbon storage, regeneration and mature trees. Forest collective action behaviors are costly and form the basis of most community forestry programs. Using our experiment, combined with regression analysis, we find significant evidence that more cooperative individuals engage in collective action behaviors that support common forests, once we adjust for demographic factors, wealth and location. Those who contribute more in the public goods experiment are found to be more likely to report that they have planted trees in community forests during the previous month and invested in biogas. They also planted more trees on their own farms, likely spent more time monitoring community forests and planted more trees in community forests. We then find that forest collective action behaviors are associated with some aspects of better forest quality and especially forest regeneration, which shows robust results across forest collective action behaviors. These results suggest that policies to support forest collective action, such as democratization of local governance, assuring fair distribution of benefits, graduated sanctions, etc., could be very important for forest quality and economic outcomes associated with forest resources.